USTAZ-SHÁKIRT DÁSTÚRLERI - Abdimuratov, P.S. (SCIENCE and SOCIETY, 2025)
The article deals with the actual problem of social and cultural competence of an English teacher and its level worth modern tendency of social development and forward ideas of pedagogical science in present.